Multifield analysis using multiple code coupling of a MEMS based micropump with biocompatible membrane materials for biomedical applications - Asim Nisar (2018)
We present multifield analysis of a MEMS based piezoelectrically actuated valveless micropump with biocompatible polymer membrane materials for drug delivery applications, A three dimensional model of the micropump is built and fluid-structure interface effects have been taken into account in finite element analysis using multifield code coupling method. The dependency of the micropump characteristics on micropump dimensions and membrane and actuator materials is investigated. The analysis predicts that there is a definite relationship between membrane and piezoelectric layer thickness to obtain maximum pump flow. Diffuser geometrical dimensions such as diffuser length, diffuser neck width and diffuser angle play a critical to enhance the performance of the micropump and need to be optimized before fabrication. © 2008 IEEE.